SLEEP DISTURBANCE AMONG CHILDREN - E.A. Abashidze; L.S. Namazova; E.V. Kozhevnikova; S.K. Arshba (Union of pediatricians of Russia, 2008)
Sleep is an important factor in the live of children and it is a vital need, essential for a child's health and growth. Children who get enough sleep are more likely to function better and they are less prone to behavioral problems and moodiness. Sleep apnea is one of the causes of sleep disorders among the children. Undiagnosed and untreated sleep apnea may contribute to daytime sleepiness and behavioral problems including difficulties at school. Сhildren are also more likely to be hyperactive and have difficulty paying attention. The polysomnography is the precise registration of the architecture and microstructure of sleep. This information allows clinicians to evaluate any apparent fluctuations in breathing, heart rate changes, or oxygen desaturations within the context of sleep physiology.Key words: sleep, sleep disorder, sleep apnea, polysomnography, children.